2019
DOI: 10.29252/jrh.9.1.11
|View full text |Cite
|
Sign up to set email alerts
|

The effect of education based on based health belief model on osteoporosis and bone mineral density among women

Abstract: Osteoporosis is a systemic skeletal disorder characterized by reduction of one mass, deterioration of bone structure, increase of bone fragility, and fracture risk increment. The purpose of this study was to investigate the effect of an educational program based on Health Melief Model (HBM) onosteoporosis and Bone Mineral Density (BMD) in women. In this quasi-experimental study, 160 participants registered with the health centers. 80 participants were randomly divided into the experimental and control groups. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
1
1
1
Order By: Relevance
“…This study's findings are consistent with those made by Kaveh, et al (2018), who looked at the impact of educational programs regarding osteoporosis prevention on students' self-efficacy in Shiraz and found that the intervention group's efficacy significantly increased following the training. Similar to Ali, et al (2019), who found that the mean scores of self-efficacy in their study demonstrated that both groups had a low ability to control food and walk, before intervention the mean self-efficacy score considerably rose in the experimental group following the intervention.…”
Section: Discussionsupporting
confidence: 81%
“…This study's findings are consistent with those made by Kaveh, et al (2018), who looked at the impact of educational programs regarding osteoporosis prevention on students' self-efficacy in Shiraz and found that the intervention group's efficacy significantly increased following the training. Similar to Ali, et al (2019), who found that the mean scores of self-efficacy in their study demonstrated that both groups had a low ability to control food and walk, before intervention the mean self-efficacy score considerably rose in the experimental group following the intervention.…”
Section: Discussionsupporting
confidence: 81%
“…Inconsistent to other studies, 29,30 coffee drinking and carbonated beverages are quite prevalent among studied females, although they knew them as risk factors, where they consumed them more frequently either in those with good or poor knowledge. Notes: *P≤0.05 is significant; a only females who were exposed outdoors, b who use only sun block.…”
contrasting
confidence: 91%
“…The recommendation of CRC screening to both men and women also provides an opportunity for gender analysis and comparison. Although some studies in public health have assessed the effect of social support on CRC screening uptake (Dominic et al., 2020; Dong & Liu, 2017; Khani Jeihooni et al., 2017; Kinney et al., 2005; Rogers et al., 2017; Takahashi & Nakao, 2021), these have been limited in terms of geographic scope, sample sizes or a focus on specific ethnic groups. Moreover, they have not addressed gender differences in the effect of social support on CRC screening uptake.…”
Section: Introductionmentioning
confidence: 99%